La comunicación en organizaciones no lucrativas: la experiencia de “Prevensud” - Castro de la Cueva, Jorge Daniel (2014)
This paper aims to develop the systematization of the experience of the "Prevensud" Foundation that for seven year it has been developing for a project on sexual and reproductive health directed to all audiences making a strong focus on adolescents and youth. The development of this work allows to raise the knowledge and vision people neeed to have regarding these organizations, and their work the do in favor of the vulnerable and those at risk in our country. The first chapter outlines the road taken to the "Communication and Development" starting from the beginning up to the present and its main focus on projects in Sexual and Reproductive Health (SRH) in the country, for which is necessary to mention the mainstream of communication.